Quantitative genetics analysis and progeny testing of Deli dura × Serdang-AVROS pisifera for long stalk characteristic - W Rusik, Wan Rusydiah (2019)
The oil palm plantations are a labour-intensive industry and to reduce dependency on labour, work process improvement by adopting technologies and machines need to be done. However, there are no harvesting machine that is as cost effective, efficient and dependable as the human harvester. Longer bunch stalk was believed to ease harvesting the fresh fruit bunch (FFB) either by machine or by manual. It eases the harvesting process as there are gaps between the bunch and the petiole bases. A total of nine oil palm Deli dura × Serdang-AVROS pisifera (D×P) derived from the North Carolina Mating Design 1 (NCM1) were evaluated at Dusun Durian Estate, Banting, Selangor. The Deli dura in this study originated from Banting dura and were crossed with Serdang- AVROS pisifera. The materials were evaluated for yield and yield components, bunch quality, vegetative traits and bunch stalk length. The data were collected from April 2009 to March 2018. The main objective of this study was to identify bunch stalk length of more than 25 cm in Deli dura × Serdang-AVROS pisifera progeny and Serdang-AVROS pisifera male parent to be commercialized and used as planting material. The specific objectives of the study were to evaluate the performance of Deli dura × Serdang-AVROS pisifera progenies for yield and yield components, bunch quality, vegetative traits and bunch stalk length, to evaluate general combining ability (GCA) of parents for stalk length trait through progeny testing, to estimate genetic variability and heritability, to assess correlation between stalk length with traits of economic importance and to analyse path coefficient analysis between all the traits studied with oil yield. Analysis of variance (ANOVA) in full-sib families showed that significant amount of genetic variability exists among Deli dura × Serdang-AVROS pisifera progenies yield and yield components, bunch quality, vegetative traits and bunch stalk length. The genetic variability is important for a successful breeding and selection. The yield and bunch quality performance of Deli dura × Serdang- AVROS pisifera progenies were comparable with Deli dura × AVROS pisifera planted in the same trial as control. ANOVA showed that the Pisifera item in the half-sib families was significant to almost all traits except mean fruit weight (MFW), oil-to-dry mesocarp (%O/DM) and oil-to-wet mesocarp (%O/WM). The result was expected as male parents are coming from the combination of two male populations; Serdang and AVROS. Mean stalk length of the nine progenies studied were ranged from 20.66 to 26.93 cm. Progeny BM 4340, BM 4344 and BM 4351 had bunch stalk length means of more than 25 cm. From 445 palms measured, 42 individual palms had bunch stalk length more than 30 cm. Broad- sense heritability estimates for average bunch weight, mesocarp-to-fruit (%M/F), shell-to-fruit (%S/F), kernel-to-fruit (%K/F), kernel-to-bunch (%K/B), rachis length and stalk length were moderate in Deli dura × Serdang-AVROS pisifera, suggesting greater genetic control and small environmental influence. Low narrow-sense heritability estimates were observed in yield and yield components with h² of 0-8.28% and h² of 0.53-41.67%. Narrow-sense heritability n(p) n(d) estimates for bunch quality were also low with h² of 0-45.94% and h² of n(p) n(d) 1.68-24.34%. Higher narrow-sense heritability estimates were observed in vegetative traits for dura or maternal side with h² of 31.77-101.06%. n(d) Correlation between bunch stalk length and all traits were also observed in this study. Bunch stalk length correlated positively with average bunch weight, mesocarp-to-fruit and rachis length. The study suggested that, selecting for long stalk length will resulting in heavier bunch, thicker mesocarp and longer rachis length. This study has identified male parent, BM 2436/9 as the best Serdang- AVROS pisifera with high GCA for fresh fruit bunch yield, bunch number, average bunch weight, mesocarp-to-fruit (%M/F), oil-to-bunch (%O/B), oil yield per palm (O/P) and oil per hectares (O/Ha). The pisifera, BM2455/7 was the best general combiner for palm height and stalk length.